The Influence Of Compensation And Organizational Culture On Organizational Citizenship Behavior In Pengadilan Tinggi Agama Bengkulu - Putri Handayani; Sri Ekowati (Journal of Indonesian Management, 2024)
This study aimed to determine the effect of compensation and organizational culture on organizational citizenship behavior of employees in Religious High Court of Bengkulu. The object of this study was 55 employees of Religious High Court of Bengkulu. The data collection technique of this study used observation. interview, and questionnaire. The data analysis techniques used instrument tests, classical assumption tests, analysis of respondent responses, multiple linear regression analysis, coefficient of determination, and also hypothesis testing. The research results show that compensation has a positive and significant effect on organizational citizenship behavior of employees in Religious High Court of Bengkulu. The organizational culture has a positive and significant influence on organizational citizenship behavior of employees in Religious High Court of Bengkulu. So, from the results of the research that has been conducted, it can be concluded that compensation and organizational culture have a partial and simultaneous effects on organizational citizenship behavior of employees in Religious High Court of Bengkulu.